Peran Partisipasi Paguyuban Masyarakat dalam Perancangan Desain Koridor Jalan Utama dalam Menujang Pariwisata Kampung Batik Wiradesa - Rizka Arinta; Astari Wulandari; Choirul Amin; Wayan Widhiantara (Universitas Lancang Kuning, 2022)
Kampung Batik Wiradesa Pekalongan as an area with potential for batik cultural heritage in 3 countries has a special attraction for tourism development in the city of Pekalongan. The Main Corridor Design is the first visual that can attract a tourist attraction. The magnitude of the potential that exists in this batik village, both from a social perspective as well as local wisdom of batik 3 from the Pekalongan country demands the role of urban designers in providing design planning solutions that involve community participation. This program is implemented in 4 weeks using the participatory design design method. The design process does not only come from observation of the design but also from the point of view of the community who helped develop the wiradesa batik village. Based on the results of discussions with residents, a road corridor design was produced which has characteristics such as the presence of ornaments. So that the resulting design is a collaborative design that fits the needs of the place.